CALCULATION OF CO2 AND O2 NEEDS AS WELL AS CO2 ABSORPTION AND O2 PRODUCING IN ZONE 5 GREEN OPEN SPACES YOGYAKARTA STATE UNIVERSITY - Mega Kurniawati; Retna Hidayah; Mahdika Putra Nanda; Ni Putu Diah A. Permanasuri (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2024)
Carbon dioxide (CO2) produced by smoke can produce humans if there are no trees or green open spaces that can absorb CO2 and emissions resulting from human activities. Therefore, efforts to reduce air pollution such as CO2 gas in the campus environment, especially Zone 5 of Yogyakarta State University are ways to build green open spaces. This study suggests to calculate the amount of CO2 emitted and the amount of O2 needed in Zone 5 of Yogyakarta State University that emits emissions from vehicles that are channeled and breathed by humans equipped with functions that absorb CO2 and produce O2. The estimation results show that total CO2 emissions in Zone 5 of Yogyakarta State University in 2019 were 7,479,066 tons / year while the demand for O2 in Zone 5 of Yogyakarta State University in 2019 was 6,763,027 tons / year. So the ability of green open space to absorb CO2 is 3.070,1308 tons/ year and the ability to produce O2 is 131,807 tons / year